Genetic risk factors for overuse and acute musculoskeletal injuries - Hill, Lee-Devlin (Department of Human Biology, 2025)
Both acute and chronic tendon and ligament injuries are multifactorial that are the result of a combination of a poorly understood complex interaction of several intrinsic and extrinsic risk factors. There is a growing body of evidence suggesting that inherited genetic elements may predispose an individual to injury risk and should therefore be considered as important intrinsic risk factors. Previous studies have investigated the association several collagen gene (COL1A1, COL5A1, COL6A1, COL11A1, COL11A2 and COL12A1) variants with chronic lower limb tendinopathies, such as Achilles tendinopathy, and other exercise-associated phenotypes involving the musculoskeletal system. These genes encode for important structural components of both tendons and ligaments and have been proposed to influence the inter-individual variation in the biomechanical properties of these tissues. The association of these collagen gene variants with rotator cuff tendinopathy (RCT), more specifically supraspinatus tendinopathy (SST), has not been extensively investigated. Except for COL1A1 variants, the association of the remaining collagen gene variants with an acute injury, such as anterior cruciate ligament (ACL) ruptures, has also not been extensively investigated. AIMS Therefore, the primary aim of this thesis was to investigate the association of the COL1A1 rs1800012 (G/T), COL5A1 rs12722 (T/C), COL5A1 rs10628678 (AGGG/-), COL6A1 rs35796750 (T/C), COL11A1 rs3753841 (T/C), COL11A1 rs1676486 (C/T), COL11A2 rs1799907 (A/T) and COL12A1 rs970547 (G/A) gene variants with RCT in a South African cohort of swimmers (Chapter 4), as well as ACL rupture in a combined cohort of European ancestry (Swedish, South African, Polish and Australian) (Chapter 5) and a South African Mixed Ancestry cohort (Chapter 6) using a case-control genetic association study approach. A secondary aim of the thesis was to investigate hypothesis-driven collagen gene-gene interactions between the investigated variants in modulating the risk of injury in the different RCT (Chapter 4) and ACL (Chapters 5 and 6) cohorts. Finally, a systematic review of the risk factors associated with RCT in swimmers was also included in this thesis (Chapter 3). METHODS For chapter 4, 103 (49 females, 54 males) swimmers with clinically diagnosed rotator cuff tendinopathy (RCT group) were recruited of the 103 participants in the RCT group, 84.5% (n=87) were diagnosed with a supraspinatus tendinopathy (SST) and were analysed separately as a sub-group. In addition, 101 (55 females,46 males) apparently healthy swimmers with no previous history of shoulder pathology (including RCT, trauma, bursitis, or adhesive capsulitis) (CON group) were recruited. All participants were unrelated, of self-reported European ancestry and recruited between 2013 and 2016. For Chapter 5, 195 physically active and unrelated participants of self-reported European ancestry were recruited between 2011 and 2013 from the University Hospital in Umeå and orthopaedic clinics in Luleå, Sweden. These participants within this cohort comprised of 79 individuals who had clinically diagnosed ACL injuries with a non-contact mechanism of rupture (NON group) and 116 apparently healthy, asymptomatic individuals with no history of ACL injuries (CON group). The Swedish cohort was included in a larger combined analysis consisting of 661 participants with ACL rupture and 378 uninjured controls from previously published cohorts of self-reported European ancestry from South Africa, Poland, and Australia. For chapter 6, 209 unrelated participants with self-reported mixed ancestry participants were included in this study. The participants were previously recruited between January 2012 and May 2016 from Groote Schuur Hospital, Victoria Hospital, and the Sports Science Orthopaedic Clinic within the Cape Town, South Africa. Ninety-four participants (77 males and 17 females) were included in the ACL group, of which 51 had sustained their ACL rupture through a non contact mechanism of injury (NON sub-group. Furthermore, 100 (81 males and 19 females) apparently healthy, individuals with no history of ACL rupture or injury were recruited from gyms and local sports clubs within the Cape Town area of South Africa. All participants were genotyped for the following collagen gene polymorphisms: COL1A1 rs1800012 (G/T), COL5A1 rs12722 (T/C) and rs10628678 (AGGG/-), COL6A1 rs35796750 (T/C), COL11A1 rs3753841 (T/C) and rs1676486 (C/T), COL11A2 rs1799907 (A/T) and COL12A1 rs970547 (G/A). RESULTS As presented in a systematic review of non-genetic risk factors (Chapter 3), only four risk factors for shoulder injuries were determined to be of moderate certainty, with the remaining 25 risk factors being appraised as low certainty. Moderate level of certainty was determined in (i) previous history of pain and injury, (ii) internal/external rotation range of motion, (iii) clinical joint laxity and instability and (iv) internal/external rotation strength. Although previously associated in some studies investigating other overuse musculoskeletal soft tissue injuries, none of the investigated collagen variants were independently associated with rotator cuff tendinopathy (RCT) or supraspinatus tendinopathy (SST) risk (Chapter 4). A novel finding of this thesis was that the C-A-(-) inferred haplotype constructed from COL11A1 rs3753841(T/C), COL11A2 rs1799907 (A/T) and COL5A1 rs10628678 (AGGG/-) was found to be significantly over-represented in the CON group (6.0 %) compared to the SST (0.4 %) groups (p=0.034). However, none of the inferred haplotypes constructed from (i) the two COL5A1 variants, (ii) the two COL11A1 variants, (iii) the three COL11A1 and COL11A2 variants, as well as all (iv) the COL11A1, COL11A2 and COL5A1 variants were associated with RCT or SST risk. Similarly inferred haplotypes constructed from (i) COL5A1 and COL6A1, (ii) COL5A1 and COL12A1, as well as (iii) COL6A1 and COL12A1 were also not associated with RCT or SST. The COL1A1 rs1800012 TT genotype was found to be significantly (p=0.027) under represented in the ACL (GG 68.0%, GT 30.9%, TT 1.1%) group of European ancestry during the combined analysis compared to the CON group (GG 67.0%, GT 29.0%, TT 4.0 %). A novel finding of this thesis was that this association was only observed in female (p = 0.045, OR = 0.00, CI 0.00 – 0.71; ACL: GG 68.1%, GT 31.9%, TT 0.0%; CON: GG 68.3%, GT 27.0%, TT 4.8%) but not male (p =0.299; ACL: GG 68.0%, GT 39.5%, TT 1.5%; CON: GG 66.5%, GT 31.0%, TT 3.6%) ACL groups. Although independently associated with ACL rupture in European populations, the COL1A1 rs1800012 TT genotype was however not significantly associated with ACL rupture in the Mixed Ancestry cohort (ACL: 85.4% GG, 13.5% GT and 1.0% TT vs CON: 82.3% GG, 17.7% GT and 0.0% GG, p=0.204). An additional novel finding was that the COL12A1 rs970547 polymorphism was significantly associated with risk in a South African Mixed Ancestry ACL rupture cohort (NON: 34.9% AA, 44.2% GA and 20.9% GG vs CON: 34.4% AA, 60.2% AG and 5.4% GG, p=0.021). This variant was however not associated with ACL rupture in the European populations (ACL: AA 63.7%, GA 31.3%, GG 5.1%) compared to the combined CON group (CON: AA 60.4%, GA 35.3%, GG 4.3%, p=0.423). None of the other investigated collagen gene variants were independently associated with ACL rupture in the European or mixed ancestry cohorts. Within participants of European ancestry, the C-AGGG (31.2% ACL vs 20.6% CON, p=0.001) and T-(-) (14.4% ACL vs 5.7% CON, p=0.010) inferred haplotypes constructed from COL5A1 rs12722 (C/T) and rs10628678 (AGGG/-) were significantly over-represented in the ACL rupture group. On the other hand the T-AGGG inferred haplotype was significantly (p>0.001) over-represented in the CON group (50.5%) compared to the ACL group (36.6%). None of the COL5A1 inferred haplotypes were however significantly associated with ACL rupture in the South African mixed ancestry cohort. A further novel finding was a significant interaction between the COL6A1 rs35796750 and COL12A1 rs970547 variants, the T-A inferred haplotype was significantly (p=0.030) over represented in the ACL group (11.0%) compared to the CON group (7.1%) when the participants of European ancestry were analysed. The T-G inferred haplotype was significantly (p=0.010) over-represented in the male CON sub-group (33.7%) compared to the male ACL sub group (23.0%) in the participants of European ancestry. Within the South African mixed ancestry population, the C-G inferred haplotype constructed from the COL6A1 and COL12A1 variants was significantly (p=0.029) over-represented in the ACL group (37.2%) compared to the CON group (31.1%). This haplotype remained significantly (p=0.027) associated when only the participants with a non-contact mechanism of injury (34.3% NON sub-group) was analysed. Finally, the inferred T-A haplotype constructed from COL5A1 rs12722 and COL12A1 rs970547 was significantly (p=0.039) with ACL rupture (27.3% ACL vs 17.9% CON) in the combined European cohort associated with risk. CONCLUSION This thesis investigated collagen gene variants that have been previously associated with a number of injury phenotypes and other exercise-related conditions in three independent cohorts. Whilst only two variant were found to be independently associated with risk, several gene-gene interactions were observed, demonstrating the complex and multifactorial nature of the MSK injuries. These novel findings therefore draw attention to the possible important role that genetic factors in the aetiology of tendon and ligament pathologies. Furthermore, this thesis highlights the importance of conducting studies in non-European and genetically diverse populations.